2013
DOI: 10.5120/13758-1597
|View full text |Cite
|
Sign up to set email alerts
|

Missing Numbers in K-Graceful Graphs

Abstract: The generalization of graceful labeling is termed as-graceful labeling. In this paper it has been shown that , is-graceful for any (set of natural numbers) and some results related to missing numbers for-graceful labeling of cycle , comb , hairy cycle and wheel graph have been discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Maheo and Thuillier [10] have shown that cycle C n is k-graceful if and only if either n ≡ 0 or 1(mod4) with k even and k ≤ (n − 1)/2 or n ≡ 3(mod4) with k odd and k ≤ (n 2 − 1)/2, while P. Pradhan and et al [11] have shown that cycle C n , n ≡ 0(mod4) is k-graceful for all k ∈ N (set of natural numbers). Maheo and Thuillier [10] have also proved that the wheel graph W 2k+1 is k-graceful and conjecture that W 2k is k-graceful when k ̸ = 3 or k ̸ = 4.…”
Section: Introductionmentioning
confidence: 99%
“…Maheo and Thuillier [10] have shown that cycle C n is k-graceful if and only if either n ≡ 0 or 1(mod4) with k even and k ≤ (n − 1)/2 or n ≡ 3(mod4) with k odd and k ≤ (n 2 − 1)/2, while P. Pradhan and et al [11] have shown that cycle C n , n ≡ 0(mod4) is k-graceful for all k ∈ N (set of natural numbers). Maheo and Thuillier [10] have also proved that the wheel graph W 2k+1 is k-graceful and conjecture that W 2k is k-graceful when k ̸ = 3 or k ̸ = 4.…”
Section: Introductionmentioning
confidence: 99%